Temporal variability of Oscillatoria sp. in extreme environment: a sulfide-rich spring outflow - Reul, Andreas; Martín-Clemente, Elena; Melero-Jiménez, Ignacio José; Hernández-López, Miguel; Toro-Gil, Francisco Javier; Bañares-España, Elena; Flores-Moya, Antonio; García-Sánchez, María Jesús; Melero-Jiménez, Ignacio José (My University, 2017)
Backgrounds The Hedionda Spa (Andalucía, southern Spain) is a sulfide-rich spring outflow, but despite the inhibitory effect of sulfide on photosynthesis, a phytoplankton community inhabits this extreme environment. Objectives To analize the phytoplanktonic groups present in La Hedionda Spa along an annual cycle, and to study the possible correlation between sulphide concentration and the presence of different groups. Methods A monthly and weekly sampling was started on March 2016. Samples were analyzed with a fluorospectrometer to detect the presence of different groups. A FlowCAM analysis of photoplankton was carried out at 5-100 μm ESD to determine biovolume and abundance. Water samples were analized to determine sulphide concentration. Conclusions Sulphide concentrations varied from 0.8 to 219.4 μM, while chlorophyll a ranged between 0.4 and 11.7 ug l-1. Cyanobacteria is the predominant phytoplanktonic group, accounting for 50-90% of total chlorophyll. Oscillatoria sp. is the predominant cyanobacteria in terms of abundance (0.55-65.6 filamemts·ml-1) and biovolume (9·105-3·108 μm3 ml-1). A positive correlation was found between sulphide concentration and Oscillatoria sp. abundance, but not between sulphide and total chlorophyll a concentration. The positive correlation could be due to (i) dilution of both sulphide and Oscillatoria sp. abundance by runoff, or (ii) to a physiological advantage of Oscillatoria sp. under elevate sulphide, which has been confirmed in laboratory experiments. However, high sulphide might also reduce Oscillatoria sp. growth rate, but the absence of potential predator or competitor provides Oscilatoria sp. an advantage in the environment not detectable in laboratory approaches.
Keywords: Fitoplancton; Oscillatoria sp.; Phytoplankton community; Fluorospectrometer analysis; Sulphureous environment